NASKAH PUBLIKASI PENGARUH NILAI PELANGGAN, CITRA MEREK TERHADAP KEPUASAN PELANGGAN DENGAN KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING ( Studi Pada Mahasiswa Universitas Stikubank Semarang ) - Ella Nurilla Sari, 11.05.51.0123; Marlien, Marlien (Students Journal of Economic and Management, 2014)
This research is study that tested the effect of customer value and brand image on customer satisfaction with the purchase decision as an intervening variable. The population was Stikubank Semarang University student. Based on the indicators used reliability test is an indicator of the variables studied were the result unreliable or reliable. Further analysis researchers used multiple linear regression analysis to explain the relationship between these variables, the result is a positive effect on the value of the customer purchase decision and significant, which means if there is an increase in the value of the customers purchase decision will increase while the brand image on purchase decisions happen gap (gap) brand image. So that the brand image is not a determining factor purchase decision. As for the test of intervening in this study mediate and influence purchasing decisions is more dominant in the relationship of customer value on customer satisfaction. This study has limitations that sampling periods were relatively short, have not considered the main control variables and other variables that could affect customer satisfaction. Therefore, further research is recommended to consider key variables and other control variables as well as the need for longer periods of studyin order to generalize.Keywords: customer value, brand image, purchasing decisions, customer satisfaction.